2016
DOI: 10.1155/2016/8395268
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline Therapy for Nosocomial Pneumonia due to Carbapenem-Resistant Gram-Negative Bacteria in Critically Ill Patients Who Received Inappropriate Initial Antibiotic Treatment: A Retrospective Case Study

Abstract: Background. Nosocomial pneumonia due to carbapenem-resistant Gram-negative bacteria (CRGNB) is a growing concern because treatment options are limited and the mortality rate is high. The effect of tigecycline (TGC) on nosocomial pneumonia due to CRGNB in patients who have received inappropriate initial empiric antibiotic treatment (IIAT) is unclear. Therefore, this study aimed to examine the effect of TGC on nosocomial pneumonia due to CRGNB in critically ill patients who had received IIAT. Methods. A retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…[12] 3 random controlled trial, [12,34,36] among which one was a phase 2 double-blind study, [12] one described the randomization method, [34] while the other without any detail illustration, [36] 3 prospective cohort study [25,28,32] and 11 retrospective cohort study. Studies covered several different countries, including Italy (2 studies [25,26] ), Spain (2 studies [27,39] ), Brazil (1 study [28] ), China (11studies, 3 published in English, [14,31,35] and 8 in Chinese) and one international multicenter. [12]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] 3 random controlled trial, [12,34,36] among which one was a phase 2 double-blind study, [12] one described the randomization method, [34] while the other without any detail illustration, [36] 3 prospective cohort study [25,28,32] and 11 retrospective cohort study. Studies covered several different countries, including Italy (2 studies [25,26] ), Spain (2 studies [27,39] ), Brazil (1 study [28] ), China (11studies, 3 published in English, [14,31,35] and 8 in Chinese) and one international multicenter. [12]…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies [12,14,2528,31–33,35,39] reporting mortality were included for analysis. All-cause mortality for patients treated with HD tigecycline was significantly lower than LD ( RR 0.67, 95% CI 0.53–0.84, 11 studies, 629 patients) without significant heterogeneity ( P = .30, I 2 = 15%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In infected carbapenem-resistant Acinetobacter baumannii patients without appropriate empirical antimicrobial therapy, the overall mortality rate was 86.1% [21]. The ICU mortality rate was 45.2% in critically ill patients infected with CRGNB who received tigecycline therapy [22], and the in-hospital mortality rate was 62.5% [23]. The 30-day mortality in the treatment of infections due to carbapenem-resistant Enterobacteriaceae was 50% after ceftazidime-avibactam treatment [24].…”
Section: Discussionmentioning
confidence: 99%
“…The multivariate analyzes showed that the prolonged tigecycline usage was significantly associated with clinical resolution, whereas higher CURB65 scores, mechanical ventilation and tigecycline resistant to MDRAB have significant association with 30-day mortality, and these results may help to explain previous results. Many studies compared the efficacy of tigecycline in the treatment of MDRAB with other antibiotics, and tigecycline was not recommended as first line treatment for MDRAB because of the higher mortality and lower microbiological success, especially for bacteremia [68, 20]. However, further analysis showed that the increased mortality rate of tigecycline is significant higher only among those with MIC>2 mg/L, but not for those with MIC≤2 mg/L.…”
Section: Discussionmentioning
confidence: 99%